2018
DOI: 10.1093/labmed/lmy028
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Filtration Rate in Patients with Multiple Sclerosis Undergoing Stem Cell Transplantation and Treated with Cyclophosphamide

Abstract: Renal function must be monitored in patients with MS undergoing autologous stem-cell transplantation. Also, chemotherapy should be constrained as much as possible to prevent further deterioration of renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A key point in our protocol is the administration of cyclophosphamide for 2 days – 7 days apart – instead of on 4 consecutive days. The rationale hinges on three points: : to mobilize cells with cyclophosphamide for the autograft to allow the use of a refrigerated rather than a frozen autograft, and to decrease toxicity . The rapid bone marrow recovery we have observed using refrigerated blood cell grafts is concordant with our experience in individuals with plasma cell myeloma and lymphomas who received high‐dose therapy and an autotransplant .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A key point in our protocol is the administration of cyclophosphamide for 2 days – 7 days apart – instead of on 4 consecutive days. The rationale hinges on three points: : to mobilize cells with cyclophosphamide for the autograft to allow the use of a refrigerated rather than a frozen autograft, and to decrease toxicity . The rapid bone marrow recovery we have observed using refrigerated blood cell grafts is concordant with our experience in individuals with plasma cell myeloma and lymphomas who received high‐dose therapy and an autotransplant .…”
Section: Discussionmentioning
confidence: 55%
“…In hematological malignancies, we and others have shown that the mortality rate of the autografts can be substantially decreased to figures below 5% if the transplant is performed with PBSC on an out‐patient basis, and using non‐frozen, non‐thawed stem cells . After 25 years of autografting more than 1000 patients with hematological malignancies , we have now grafted patients with MS using a novel low‐intensity conditioning regimen, unlike that commonly recommended in other parts of the world. A key point in our protocol is the administration of cyclophosphamide for 2 days – 7 days apart – instead of on 4 consecutive days.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that B-cell lymphoma has some similar symptoms with MS, and early treatment with corticosteroids can improve patient symptoms in both conditions ( Lyons et al, 2012 ). We can also find more genetic or clinical links between Multiple Sclerosis and acquired immunodeficiency syndrome ( Morriss et al, 1992 ), chronic kidney disease ( Ruiz-Argüelles et al, 2019 ), papillary thyroid carcinoma ( D’Amico et al, 2019 ), HIV Infections ( Gold et al, 2015 ), type 2 diabetes mellitus ( Hussein and Reddy, 2006 ), Parkinson’s disease ( Delalić et al, 2020 ), Uterine Cervical Neoplasm ( Doosti et al, 2018 ), and Hepatitis ( Cação et al, 2018 ). Combining our findings, it can be indicated that miRNAs may play important role in various phenotypes in MS patients, and those predicted miRNAs may be potential therapeutic targets for those related diseases and symptoms after wet-lab evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] Because this was a safety rather than an efficacy study, there are limitations to interpreting our data. 14 Our finding of rapid bone marrow recovery using refrigerated blood cell grafts is like our experience in persons with plasma cell myeloma and lymphomas receiving high-dose therapy and an autotransplant.…”
Section: Discussionmentioning
confidence: 99%
“…14 Our finding of rapid bone marrow recovery using refrigerated blood cell grafts is like our experience in persons with plasma cell myeloma and lymphomas receiving high-dose therapy and an autotransplant. [15][16][17] Because this was a safety rather than an efficacy study, there are limitations to interpreting our data. For example, it was not designed to compare fractionated vs continuous cyclophosphamide nor refrigerated vs frozen grafts.…”
Section: Discussionmentioning
confidence: 99%